FLY ASH TEMPURUNG KELAPA SEBAGAI BAHAN TAMBAH PADA BETON NON STRUKTURAL - Rio Rahma Dhana; Ahmad Khoirur Riza (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2019)
The research was conducted to : (1) Knowing how the process of making coconut shell fly ash in concrete mixtures, (2) Knowing how the effect of increasing coconut shell fly ash to the compressive strength of concrete. The researcher was used experiment method. There are three samples of experiment things that used to increase the percentage of coconut shell fly ash. The size of the cylindrical mold was 15 cm and the height diameters were 30 cm. The treatment was passing for 7 days, the value of strong pressure was correlated over 28 days.  The finding research was found that the compound of coconut shell fly ash for quality concrete K-100 which affects the compressive strength of the concrete itself. From the data, it has been carried out that in this research coconut shell fly ash has increased significantly, the highest concrete coconut shell fly ash mixture 1.5% can reach a compressive strength of 31,643 MPa. At last, it can be concluded that coconut shell fly ash can be used as an added material for cement in K-100 quality concrete in the presentation above. For the next research, the researcher should do the deepest experiences to know the strength of concrete. Keywords : Concrete, Compressive Strength, Coconut Shell Fly.